Antimicrobial activity of eucalyptus essential oil against Pseudomonas in vitro and potential application in refrigerated storage of pork meat. (22nd February 2016) - Lu, Hao; Shao, Xingfeng; Cao, Jinxun; Ou, Changrong; Pan, Daodong
Abstract : Eucalyptus oil treatment showed antibacterial ability, which could be found by the modifications of ultrastructure of Pseudomonas spp. and P. aeruginosa . Pork treated with eucalyptus oil exhibited the higher sensory scores of custom acceptance than those in control at the end of cold storage. Summary: The objective of this study was to investigate the influence of eucalyptus essential oil (EO) on the Pseudomonas in vitro and application in the pork meat. Eucalyptus oil showed the greatest antimicrobial activity to Pseudomonas among five EOs (tea tree oil, eucalyptus oil, clove oil, mentha oil and garlic oil) in vitro . Eucalyptus oil treatment caused the increasing of membrane permeability and the modifications of ultrastructure and morphology of Pseudomonas spp. and P. aeruginosa . Treatment of refrigerated pork with eucalyptus oil led to a significant decrease P . spp. count, pH, total volatile basic nitrogen and 2‐thiobarbituric acid values, as well as higher sensory scores of custom acceptance than those in control at the end of cold storage. It was conclude that eucalyptus EO is a potential alternative to chemical treatment to control the spoilage and extend the shelf life of refrigerated pork meat.